Farmers Perceptions towards Joint Liability Groups on Paddy Farming of Thrissur District in Kerala - Parekkadan House, Sabu P J; Pulikottil House, Minju David P; Parekkadan House, Deepa Roy (Indian Journal of Extension Education, 2025)
To overcome the obstacles such as small landholdings, high cost of labour, shortage of credit, and modest mechanisation, collective farming initiatives like joint liability groups were launched in Kerala. Earlier research on joint liability groups in the agricultural arena of Kerala has rarely examined the effects of joint liability groups (JLGs) on the improvement of paddy cultivation. To find out the effect of JLGs, the present study has collected primary data from the Thrissur district of Kerala. The primary survey was conducted from January 2025 to April 2025. Statistical tools such as analysis of variance (ANOVA) and post-hoc tests were used to analyse the data. The findings indicated that operations of joint liability groups are effective in improving the production of paddy, reducing labour cost, and improving the marketing facilities of paddy cultivation in Thrissur district. The study recommends that the state government should support the joint liability groups to endure and triumph in paddy cultivation.